Implementasi Manajemen Peserta Didik dalam Meningkatkan Kedisiplinan Siswa di SMK Negeri 1 Cimerak - Neneng Nurmalasari; Dede Sandy Noerfauzi; Miftahul Zamil (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2023)
This study aims to determine how the implementation of student management in improving student discipline at SMK Negeri 1 Cimerak. This study uses a method with a descriptive qualitative approach. Data and information collection techniques use interview, observation and documentation studies. The results of this study are to find out how the process of student management and the conditions of discipline that occur in SMK Negeri 1 Cimerak. The implementation of student management begins with planning by planning the program to be carried out, namely the K-5 activity program (Discipline, Order, Cleanliness, Tidiness, and Beauty), then in organizing the school implements a task-sharing strategy for educators and student council administrators to implementing the program, this program is then directly implemented by the party concerned and for the K-5 program (Discipline, Order, Cleanliness, Tidiness, and Beauty) assisted by the student council administrator, and to control it the school conducts an assessment ofthe K-5 activity program (Discipline, Order, Cleanliness, Tidiness, and Beauty) which are contested for each class which is held every Friday and announced on Monday during the red and white flag raising ceremony or morning apple. These management activities have a fairly good effect on increasing student discipline, including being marked by always being seen on time in terms of entering and leaving school hours and students starting to look disciplined in dressing and doing school assignments.